Mean arterial pressure may be a valuable tool for classifying blood pressure in physically actives: A cross-sectional study among females from North India - Monika Kulshreshtha; Shivani Chandel (Clinical Epidemiology and Global Health)
Background: Hypertension is a leading global health issue. Prevention, identification, and treatment of hypertension are crucial. Recent studies found that mean arterial pressure (MAP) is better for predicting hypertension than systolic and diastolic blood pressure. Thus, this cross-sectional study compared the prevalence of hypertension among Kathak dancers and physically active non-dancers in North India as per the American Heart Association (AHA) 2017, Indian Guidelines on Hypertension (IGH) 2019, and MAP. Methods: Data on blood pressure were collected using a standardized procedure from 441 Delhi-National Capital Region females (206 Kathak dancers; 235 age-matched non-dancers). We calculated MAP using Diastolic Blood Pressure + (0.33 ∗ Pulse Pressure). The prevalence of hypertension was estimated using AHA 2017, IGH-IV 2019, and MAP. Results: The present study revealed that hypertension prevalence varies significantly as per the three guidelines in Kathak dancers and non-dancers. The highest prevalence of hypertension was found with the AHA 2017 criteria, with 13.1 % in Kathak dancers and 31.1 % in non-dancers. This prevalence was reduced to 4.9 % (Kathak dancers) and 6.4 % (non-dancers) as per IGH 2019. When MAP was used, it drastically reduced the prevalence calculated by AHA 2017 (7.2 % Kathak dancers; 17 % non-dancers) and IGH-IV 2019 (.5 % Kathak dancers; 4.3 % non-dancers). Kathak dancers had a lower prevalence of hypertension than non-dancers. Conclusion: MAP may be a more effective tool for classifying blood pressure than other methods, particularly in physically active populations. Furthermore, the therapeutic movements of Kathak dance may offer a potential preventive strategy for hypertension in the general population.